CONTENT WEBSITE “101YOUNGCEO.COM” SEBAGAI HUBUNGAN KOMUNIKASI DENGAN PELANGGAN - RICKY WIDYANANDA PUTRA (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2015)
The development of today's Internet is very fast with the faster growth of the internet it is often used to communicate . The development of the internet is so rapid impact many websites , because the websites we can access any kind of information we want via the internet . In a message delivered today can use media such as websites , because there is content on the website that serves as a medium that can provide the information conveyed to the public . Under these conditions, the basic idea appears to develop a website that has content about the entrepreneur who became a key concept in the thesis research . Because this time to be an entrepreneur is being popular among people , especially the young people who want to have an income and want to have their own business . To increase the number of entrepreneurs in Indonesia, especially among young people , now has a lot of media that provide information about entrepreneurship . However , given the information media are still very common in nature , have not touched the basic needs of employers , namely : capital , motivation and courage , network or networks , business ideas , business mentor , business and science